1987
DOI: 10.3109/00365548709032417
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mycoplasma pneumoniae from Pleural Fluid and/or Cerebrospinal Fluid: Report of Four Cases

Abstract: Mycoplasma pneumoniae was isolated from pleural exudates of 2 children with pleuropneumonia. The organism was also isolated from cerebrospinal fluid of a child with meningeal manifestations and from the cerebrospinal fluid as well as pleural exudate of another child who died 21 days after onset of disease. More extensive attempts to cultivate M. pneumoniae from nonpulmonary sites are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Among patients with probable M. pneumoniae encephalitis, respiratory symptoms occurred in all 5 children in whom M. pneumoniae was detected by PCR in the throat but not in the CSF, but in only 2 of 6 children in whom M. pneumoniae was detected in the CSF but not in the throat. The absence of respiratory manifestations has also been documented in several previous case reports of patients with encephalitis for whom PCR or culture detected M. pneumoniae in the CSF [24][25][26][27]. In a recently reported study of patients with serologically confirmed systemic infections caused by M. pneumoniae, M. pneumoniae was detected in serum by PCR in only 1 of 25 patients with pneumonia but in 10 of 17 patients without pneumonia ( ) [28].…”
Section: Discussionmentioning
confidence: 58%
“…Among patients with probable M. pneumoniae encephalitis, respiratory symptoms occurred in all 5 children in whom M. pneumoniae was detected by PCR in the throat but not in the CSF, but in only 2 of 6 children in whom M. pneumoniae was detected in the CSF but not in the throat. The absence of respiratory manifestations has also been documented in several previous case reports of patients with encephalitis for whom PCR or culture detected M. pneumoniae in the CSF [24][25][26][27]. In a recently reported study of patients with serologically confirmed systemic infections caused by M. pneumoniae, M. pneumoniae was detected in serum by PCR in only 1 of 25 patients with pneumonia but in 10 of 17 patients without pneumonia ( ) [28].…”
Section: Discussionmentioning
confidence: 58%
“…The organism has been rarely isolated in cases with CNS injury from the CSF. [19][20][21][22][23]26,31,132 Recently published series have shown a good concordance between positive CSF culture results and PCR testing; PCR achieved detection in all instances. 26 M. pneumoniae has never been isolated by CSF culture in cases of myelitis, a finding indicative of the immune pathogenesis of this entity.…”
Section: Csf Findingsmentioning
confidence: 99%
“…On the other hand complete neurologic recoveries without antibiotic therapy have been described also. 14,23,43,64 Unfortunately, the literature data that are available are not helpful in providing guidance regarding the efficacy of antibiotic therapy due to the small number of patients treated, the uncertainty regarding the natural history of untreated infection, and the failure to use an antibiotic that penetrates the blood-brain barrier in many of the reported cases. Nevertheless it is reasonable to consider antibiotic therapy for children who present with a prodromal respiratory illness in the immediate past that is consistent with direct CNS infection.…”
Section: Treatment Of M Pneumoniae Related Cns Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In prospective studies, the organism is consistently implicated in 5% to 13% of acute encephalitis cases [5,8,25] and an increased incidence has been observed during outbreaks of M. pneumoniae respiratory disease [4•, 25]. The strongest evidence linking M. pneumoniae with CNS disease is provided by case reports of individuals from whom M. pneumoniae was isolated in culture from the brain or CSF [7,13,14,16,20,23]. However, the full extent and spectrum of disease attributable to M. pneumoniae remains unknown, in part because of our incomplete understanding of the pathogenesis of extrapulmonary M. pneumoniae disease and in part because of limitations of currently available diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%